Pengaruh Media Sosial Instagram @beeruindonesia terhadap Pemenuhan Kebutuhan Informasi Perhitungan Kalori - Ratu Embun Permata Sarie; Rita Destiwati (STIE Amkop Makassar, 2023)
New media is media on internet using online technology that has a flexible character, and interactive potential, and functions privately and publicly. the appearance of social media is a form of embodiment of new media. social media give various effects on their user. Instagram is one of the social media that many people choose to share information, from advertising to only just sharing their daily activities. a lot of information can be obtained from using Instagram as a media social, including information about health sciences, calorie calculation is one of it. the purpose of this research is to identify the effect of social media Instagram @beeruindonesia on fulfilling the information needs of calorie calculations. this research used a quantitative research method by distributing questionnaires to followers of the @beeruindonesia Instagram account. data analysis technique that's used is descriptive analysis, internal successive method test, normality test, heteroscedasticity test, simple linear regression analysis, coefficient of determination test, and hypothesis test T. The research results obtained are the influence of social media (X) to significantly influence needs information (Y) 70.5%, while the remaining 29.5% is explained in other variables outside the variables of this study.